BUREAUCRACY IN BEHAVIOR ANALYSIS LICENSING SERVICES INTERFERENCE IN MAKASSAR - *, Hari; Asang, Sulaeman; *, Haselman; Ahmad, Badu (IJRDO - Journal of Applied Management Science, 2015)
This study aimed to analyze the behavior of the bureaucracy in licensing service interruption inMakassar. Research conducted at the Integrated Licensing Agency for Investment and Makassar, and theDepartment of Industry and Trade of Makassar, data collection is done through observation, interviews anddocumentation. Data were analyzed using descriptive qualitative analysis. The results showed that the behaviorof the bureaucracy in the service of licensing behavior disorders related to aspects of the organization'sobjectives in particular with regard to licensing procedures (SOP) has not been reflected in the simplicity of theprocess, because it involves two agencies and still shows the sectoral ego between them. Aspects of incentivesshould motivate employees to perform optimally, but this incentive, especially in the form of money has not beenbudgeted for the second agency. Still the number of complaints over the counter complaint at the agency showedthat the accountability of employees in the service is not running optimally. Aspects of power in the context ofthis research is the signing authority licensing process has been going on delegation of authority to the ChiefBPTPM, which were previously signed by the Mayor of Makassar. The strong patriarchal society Makassar,internal bureaucracy and the impact on public services received.